PENGARUH VOLUME PERDAGANGAN SAHAM TERHADAP RETURN SAHAM DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BEI TAHUN 2017-2020 - Ratnasari, Desy; Wahyuni, Ika; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Transportation companies are one of the sectors related to the development and economic development of countries in the world. Transportation companies are among the most important companies as the largest contributor to national development, resulting in the country's economy experiencing an increase along with the rise of increasingly sophisticated technology. The number of activities in the transportation services sector also has an impact that results in stock fluctuations. The purpose of this study was to determine the effect of Stock Trading Volume on Stock Returns with Stock Price as an intervening variable in transportation facilities listed on the IDX in 2017-2020. The population of this study is all transportation companies registered on the IDX in 2017-2020 as many as 47 companies. Sampling technique is determined by purposive sampling. Data analysis and hypothesis testing in this study using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results of direct influence hypothesis test using Smart PLS 3.0 application showed that Stock Trading Volume has a significant negative effect on Stock Price, Stock Trading Volume has a negative but not significant effect on Stock Return, Stock Price has a positive but not significant effect on Stock Return and Stock Trading Volume on Stock Return through Stock Price has a negative but not significant effect.